الأخطاء اللغوية في أسئلة الاختبارات بجامعة القصيم في ضوء علم اللغة التطبيقي: الاختبارات الورقية والإلكترونية - شتا، جمال مصطفى سيد أحمد (الجمعية المصرية للكمبيوتر التعليمي, 2020)
تهدف الدراسة إلى إيجاد السبل نحو دقة صياغة أسئلة الاختبارات وصحتها اللغوية؛ وصولا إلى فهم الطالب الصحيح لأسئلة الاختبارات؛ وسعيا إلى تحقيق الجودة الشاملة للمنتَج التعليمي الجامعي، وذلك في ضوء علم اللغة التطبيقي في مجالي تعليم اللغة وتحليل الأخطاء؛ فهي دراسة وصفية تحليلية معيارية، من خلال رصد الأخطاء اللغوية في أسئلة الاختبارات وتحليلها وتصنيفها، وبيان أسبابها، واقتراح أفضل السبل لمعالجتها وتلافيها فيما بعد. فمن المؤكد أن يركز الأستاذ على المطلوب من السؤال؛ مما قد يؤدي إلى إغفال الجانب اللغوي له أو الغفلة عنه؛ فلا ينجلي المطلوب من السؤال، في أذهان الطلاب. وكانت عينة الدراسة وحدودها من اختبارات جامعة القصيم بكليات المجتمع ببريدة، والشريعة والدراسات الإسلامية، واللغة العربية، وكليات العلوم والآداب، بجامعة القصيم؛ في الأعوام من عام 28/1429ه حتى الفصل الثاني من عام 1441ه؛ لضمان تنوع التخصص وتنوع الطلاب وتنوع واضعي الأسئلة. كما أجرى الباحث استبانة لاستطلاع آراء طلاب جامعة القصيم عام 1441ه، وزعت إلكترونيا، وتفاعل معها (1084) طالب من جميع كليات الجامعة، النظرية والعلمية. وتناولت الدراسة أخطاء الاختبارات الورقية والإلكترونية من خلال ثلاثة مباحث، الأول: الأسباب التي أدت إلى وقوع الأخطاء اللغوية في أسئلة الاختبارات، والثاني: تجميع الأخطاء وتصنيفها إلى أخطاء صوتية وصرفية ونحوية ودلالية، وتصويبها. والثالث: وضع خطتين استراتيجيتين للعلاج، إحداهما سريعة التنفيذ، تقع على عاتق القيادات الإدارية في الجامعة، والأخرى تنفذ-على المدى البعيد-أثناء تعليم اللغة. وتوصلت الدراسة إلى كثرة وقوع الأخطاء الكتابية في الاختبارات، وأنها تؤثر في أداء الطلاب لتلك الاختبارات، وأن الإسراع في كتابة الأسئلة، ونسيان القاعدة، واللامبالاة في الصياغة، والقياس الخاطئ، وتداخل اللهجة مع اللغة-من الأسباب التي أدت إلى حدوث الأخطاء اللغوية في الاختبارات، وبنت على ذلك سبل علاجها.
The study aims to find ways towards accurate formulation of test questions and their linguistic validity. Up to the student's correct understanding of the test questions; In order to achieve the overall quality of the university educational product, in light of applied linguistics in the fields of language teaching and error analysis; It is a standard analytical descriptive study, by monitoring linguistic errors in test questions, analyzing and classifying them, stating their causes, and proposing the best ways to address and avoid them later. The professor is sure to focus on what is required of the question; Which may lead to neglecting the linguistic aspect of it or being overlooked. The required question does not disappear in the minds of the students. The study sample and its limits were from Qassim University tests at Buraidah Community Colleges, Sharia and Islamic Studies, the Arabic language, and the Faculties of Science and Arts, Qassim University. In the years from 1429/28 AH until the second semester of 1441 AH; To ensure the diversity of the major, the diversity of the students and the diversity of the questioners The researcher also conducted a questionnaire to survey the views of Qassim University students in 1441 AH, and it was distributed electronically, and (1084) students from all the university’s colleges interacted with it, both theoretical and scientific. The study dealt with Paper and electronic tests through Three sections, the first: the reasons that led to the occurrence of linguistic errors in the test questions, and the second: the collection of errors and their classification into phonemic, morphological, grammatical and semantic errors, and correcting them. And the third: setting up two strategic plans for treatment, one of which is quick to implement, and falls on the responsibility of the administrative leaderships at the university, and the other is implemented - in the long term - during language teaching. The study found that there are many written errors in the tests, and that they affect the students' performance of those tests, and that the speedy writing of the questions, forgetting the rule, indifference in the wording, the wrong measurement, and the overlap of the dialect with the language - are the reasons that led to the occurrence of linguistic errors in the tests, And based on that means of treatment.
Keywords: الأخطاء اللغوية -- الاختبارات الورقية -- المؤسسات التعليمية